2014
DOI: 10.1188/14.onf.297-306
|View full text |Cite
|
Sign up to set email alerts
|

Supportive Care Needs After Gynecologic Cancer: Where Does Sexual Health Fit in?

Abstract: Personal perceptions of the implications and meaning of sexual health and vaginal changes create the subjective experience of a need. Discussions of the women's perceptions of their needs and their views of healthy sexuality will help develop effective treatment plans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 41 publications
0
26
1
10
Order By: Relevance
“…Several reviews [6][7][8][9] as well as original studies [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] have described the prevalence of different supportive care needs in both breast and gynecological cancer. In previous research, the need for additional medical information on the disease has been consistently reported to be highly prevalent in both breast [6,10,16,17,29] and gynecological cancer [7,9,10,12,13,16,24,25,27].…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews [6][7][8][9] as well as original studies [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] have described the prevalence of different supportive care needs in both breast and gynecological cancer. In previous research, the need for additional medical information on the disease has been consistently reported to be highly prevalent in both breast [6,10,16,17,29] and gynecological cancer [7,9,10,12,13,16,24,25,27].…”
Section: Introductionmentioning
confidence: 99%
“…We found only one dyadic intervention for women and their caregivers. Given the significant psycho-sexual effects of gynaecological cancer (McCallum et al, 2014), the high prevalence of concern about the worries of those close to them for both women with gynaecological cancer (Beesley et al, 2008;McCallum et al, 2014) and their caregivers (Butow et al, 2014;Stafford & Judd, 2010) and the desire for 65% of partners to be involved in sexual healthcare provision (Vermeer et al, 2014), it is critical that future interventions consider patient-caregiver dyad and how their collective and individual needs related to issues specific to gynaecological cancer can be best addressed.…”
Section: Discussionmentioning
confidence: 99%
“…studies have found that sexual problems are common among patients with female cancers and one of the main issues of concern following treatment [34][35][36]. However, sexuality and intimate issues are often unmet in the healthcare system and support from patient questionnaires are suggested to be especially valuable [34]. The disease-specific modules covering the sexuality and intimate aspects were, however, not predictive of goal setting.…”
Section: Discussionmentioning
confidence: 99%
“…Our patients' motivation for health-related behavioural changes when diagnosed with cancer therefore underlined the importance of clarification of the roles of the different health care sectors. studies have found that sexual problems are common among patients with female cancers and one of the main issues of concern following treatment [34][35][36]. However, sexuality and intimate issues are often unmet in the healthcare system and support from patient questionnaires are suggested to be especially valuable [34].…”
Section: Discussionmentioning
confidence: 99%